Issues of comparability and recognition of qualifications of higher education in Kazakhstan - Abylaiuly, A.; Ibraeva, A.B. (Middle-East Journal of Scientific Research 17 (1), 84-90, 2013)
The article analyzes the international norms of recognition of higher education qualifications, their application sphere and the role of UNESCO in organizing of cooperation of states in recognition of foreign diplomas. On the basis of research, the authors concluded that the legislation of Kazakhstan does not conform to regional regulations of recognition of qualifications and the principles of the Bologna process. And also, were found contradictions in the understanding of the doctoral degree and its place in the higher education system of Kazakhstan.
Keywords: Degree; Higher education; Nostrification; Qualification; Recognition; Unesco